(1+tanx)/(1+cotx) = tanx(1+tanx) / tanx(1+cotx)
= tanx(1+tanx) / (1+tanx)
= tanx
For this question, they want me to use fundamental trig identities to simplify the expression. The problem is as follows; (tanx/csc^2x + tanx/sec^2x)(1+tanx/1+cotx) - 1/cos^2x
I got as far as this; tanx(1/csc^2x + 1/sec^2x)(1+tanx/1+cotx) - sec^2x. I factored out the tangent and simplified the 1/cos^2x to sec^2x. Then I simplified further by saying that tanx(sin^2x+cos^2x)((1+tanx/1+cotx)-sec^2x. just not sure how to simplify down the 1+tanx/1+cotx. Some help would be much obliged
5 answers
I am going to insert some necessary brackets where I think they probably should be:
tanx(1/csc^2x + 1/sec^2x)((1+tanx)/(1+cotx)) - sec^2x
= tanx(sin^2 x + cos^2 x)(1+tanx)/(1+cotx) - (tan^2 x + 1)
= tanx (1)(1+tanx)/(1+cotx) - tan^2x - 1
check your typing, this does not reduce to the answer you stated.
tanx(1/csc^2x + 1/sec^2x)((1+tanx)/(1+cotx)) - sec^2x
= tanx(sin^2 x + cos^2 x)(1+tanx)/(1+cotx) - (tan^2 x + 1)
= tanx (1)(1+tanx)/(1+cotx) - tan^2x - 1
check your typing, this does not reduce to the answer you stated.
Ok, picking up from oobleck's
(1+tanx)/(1+cotx) = tanx, we get
tanx (tanx) - tan^2 x -1
= -1 , which would not be the answer you gave.
(1+tanx)/(1+cotx) = tanx, we get
tanx (tanx) - tan^2 x -1
= -1 , which would not be the answer you gave.
i never gave a final answer just as far as i got.
oobleck are you able to explain what identities you used to break down that part? I'm just not seeing how it was simpified
oobleck are you able to explain what identities you used to break down that part? I'm just not seeing how it was simpified
looks like oobleck is not online, so I will explain
As he has shown, he has multiplied top and bottom by tan x
(1+tanx)/(1+cotx) = tanx(1+tanx) / tanx(1+cotx)
left the top as is, but expanded the bottom, realize that tanxcotx = 1
= tanx(1+tanx) / (1+tanx)
so the bottom becomes tanx + 1, cancels the top 1+tanx, leaving tanx
As he has shown, he has multiplied top and bottom by tan x
(1+tanx)/(1+cotx) = tanx(1+tanx) / tanx(1+cotx)
left the top as is, but expanded the bottom, realize that tanxcotx = 1
= tanx(1+tanx) / (1+tanx)
so the bottom becomes tanx + 1, cancels the top 1+tanx, leaving tanx